The effect of e-service quality on e-loyalty of Islamic banking customers: Does e-satisfaction act as mediator? - M. Rafi Rezeki; M. Shabri Abd. Majid; Salina H. Kassim (Jurnal Ekonomi dan Keuangan Islam, 2023)
Purpose – This study aims to measure and analyze the mediating role of e-satisfaction on the effect of e-service quality on e-loyalty of the customers of Bank Syariah Indonesia (BSI) in Banda Aceh, Indonesia. Methodology – This study gathered the primary data by distributing questionnaires to a number of 200 BSI customers that were selected as the respondents of the study using a purposive sampling technique. A Structural Equation Modelling (SEM) technique is used to test the four proposed hypotheses. Findings – The study recorded that e-service quality has positively affected the e-satisfaction and e-loyalty of the BSI customers, respectively. E-satisfaction enjoyed by banking customers has enhanced their e-loyalty. In addition, the study documented that e-satisfaction has a partial mediating effect on the relationship between e-service quality and the BSI customers’ e-loyalty. Implications – The findings of the study suggest that to promote the customers’ e-loyalty, the BSI management should focus on improving customers’ e-satisfaction by strengthening e-service quality. Originality – This study explored the mediating role of e-satisfaction on the effect of e-service quality on e-loyalty, focusing on the users of e-banking facilities of the largest Islamic banking institution in Indonesia. Therefore, this study provides significant guidelines for the Islamic banks in maintaining and enhancing e-loyalty of customers through improving their customer satisfaction by providing a high quality of services digitally nationwide.